2021
DOI: 10.3390/antiox10020232
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase Multigene Family from a Primitive Chondrostean Sturgeon, Acipenser baerii: Molecular Characterization, Evolution, and Antioxidant Defense during Development and Pathogen Infection

Abstract: Three distinct superoxide dismutases (SODs)—copper/zinc-SOD (SOD1), manganese-SOD (SOD2), and extracellular copper/zinc-SOD (SOD3)—were identified from a primitive chondrostean fish, Acipenser baerii, enabling the comparison of their transcriptional regulation patterns during development, prelarval ontogeny, and immune stimulation. Each A. baerii SOD isoform (AbSOD) shared conserved structural features with its vertebrate orthologs; however, phylogenetic analyses hypothesized a different evolutionary history f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…Interestingly, SOD has three isoforms which are characterised by cellular localization and metal co-factors such as Zn-Cu-SOD. It is present in the cytosol as SOD-1, second is Mn dependent SOD located in mitochondria (Mn-SOD) called as SOD-2 and last one extracellular Cu/Zn SOD, located within the extracellular matrices of tissues (EC-SOD; SOD-3) 62 , 63 . SOD is also playing crucial roles for development and maintenance of a homeostatic balance between the innate immune response and antioxidant defenses 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SOD has three isoforms which are characterised by cellular localization and metal co-factors such as Zn-Cu-SOD. It is present in the cytosol as SOD-1, second is Mn dependent SOD located in mitochondria (Mn-SOD) called as SOD-2 and last one extracellular Cu/Zn SOD, located within the extracellular matrices of tissues (EC-SOD; SOD-3) 62 , 63 . SOD is also playing crucial roles for development and maintenance of a homeostatic balance between the innate immune response and antioxidant defenses 64 .…”
Section: Discussionmentioning
confidence: 99%
“…However, our study did not observe a complete agreement between the level of antioxidant enzyme activity and its gene expression level. Researchers have reported that there is no strictly linear relationship between them [ 55 ]. Therefore, further studies are needed regarding the regulatory relationship between enzyme activity and genes.…”
Section: Discussionmentioning
confidence: 99%
“…Excess formation of reactive oxygen species (ROS) is partly responsible for the methotrexate induced liver injury. Fortunately, liver cells have both enzymatic and non-enzymatic defenses against ROS to maintain the redox balance (C. H. Kim, Kim, and Nam 2021). Superoxide dismutases (SODs) are a family of enzymes that act as the first line of defense against ROS in the enzymatic defense system.…”
Section: Discussionmentioning
confidence: 99%